2019
DOI: 10.1016/j.neubiorev.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of limbic seizures: Potential mechanisms and prospects of chronotherapy for mesial temporal lobe epilepsy

Abstract: Mesial Temporal Lobe Epilepsy (mTLE) characterized by progressive development of complex partial seizures originating from the hippocampus is the most prevalent and refractory type of epilepsy. One of the remarkable features of mTLE is the rhythmic pattern of occurrence of spontaneous seizures, implying a dependence on the endogenous clock system for seizure threshold. Conversely, circadian rhythms are affected by epilepsy too. Comprehending how the circadian system and seizures interact with each other is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 194 publications
(226 reference statements)
0
22
0
3
Order By: Relevance
“…The core-clock genes not only regulate the circadian rhythms (14,15) but also contribute to epileptic susceptibility. The core-clock genes can disrupt the neuronal inhibitory and the excitatory balance rhythmically, leading to seizure periodicity (16)(17)(18). In a post-status epilepticus animal model of mesial temporal lobe epilepsy, the expression of core-clock genes is found to be dysregulated during epileptogenesis: the expression of PER1 and CRY1 increases in the early post-status epilepticus condition compared to the control condition and decreases to the baseline level in epileptic condition; the expression of BMAL1, CLOCK, and CRY2 gradually decreases during epileptogenesis (17).…”
Section: Core-clock Gene and Epilepsymentioning
confidence: 99%
“…The core-clock genes not only regulate the circadian rhythms (14,15) but also contribute to epileptic susceptibility. The core-clock genes can disrupt the neuronal inhibitory and the excitatory balance rhythmically, leading to seizure periodicity (16)(17)(18). In a post-status epilepticus animal model of mesial temporal lobe epilepsy, the expression of core-clock genes is found to be dysregulated during epileptogenesis: the expression of PER1 and CRY1 increases in the early post-status epilepticus condition compared to the control condition and decreases to the baseline level in epileptic condition; the expression of BMAL1, CLOCK, and CRY2 gradually decreases during epileptogenesis (17).…”
Section: Core-clock Gene and Epilepsymentioning
confidence: 99%
“…The BMAL1 gene, which codes for the binding partner of CLOCK to form the transcription CLOCK-BMAL1 complex, is also directly involved in epilepsy as proven by animal research (33). Leite Goes Gitai et al (34) reported that, for mesial temporal lobe epilepsy patients, the imbalance of core clock genes in the epileptic hippocampus may affect the phase and amplitude of different genes that play roles in the electrical activity of neurons with consequences on the rhythmic fluctuation in the inhibitory/excitatory imbalance. The results of Matos et al (35) also showed that altered temporal expression of the clock genes after a post-status epilepticus model suggests that clock genes may be involved in epilepsy.…”
Section: Clock Genesmentioning
confidence: 99%
“…Poznanie zasad w jaki sposób zegar biologiczny moduluje próg pobudliwości drgawkowej mogłoby stać się podstawą do szukania nie tylko sposobów diagnostyki ale i zasad leczenia padaczki. W niektórych doniesieniach dotyczących obserwacji napadów limbicznych a zwłaszcza ich cykliczności podkreśla się, że minimalizacja dysfunkcji genów zegara biologicznego i zmniejszenie skutków dysregulacji/desynchronizacji może być sposobem na odpowiednie postępowanie terapeutyczne [40]. Dys-funkcje w działaniu genów zegarowych opisywano także w badaniach eksperymentalnych.…”
Section: Zmienność Czynności Bioelektrycznej Mózguunclassified
“…Czy zmiany rytmiczności okołodobowej w leczeniu padaczki mogą być zasługą stosowania melatoniny, odpowiedniej diety, naświetlenia, aktywności fizycznej? Czas i dalsze badania pokażą [40]. A może po prostu wykorzystanie niektórych leków przeciwpadaczkowych np.…”
Section: Zmienność Czynności Bioelektrycznej Mózguunclassified
See 1 more Smart Citation